Climate change & technology transfer: Barriers, technologies and mechanisms - Amrita Goldar; Shubham Sharma; Viraj Sawant; Sajal Jain (Indian Council for Research on International Economic Relations (ICRIER), 2019)
Technology transfer is one of the most contentious issues in international negotiations on climate change. Despite its recognition at international platforms such as the United Nations Framework Convention on Climate Change, G20, etc., the independent review of Climate Technology Centre and Network (CTCN), the operational arm of the UNFCCC's Technology Mechanism, shows the lack of success in the transfer of environmentally sound technologies. This study examines the barriers to technology transfer and suggests strategies to improve current technology transfer frameworks. While finance is the biggest barrier stated by countries worldwide, the ability to absorb technologies is an equally important factor as is evident from case studies from India. Apart from finance, barriers could arise due to the mode of transfer, the nature of technologies, the sectors (such as energy and transport) in which such technology is sought, intellectual property rights, etc. The study analyses the OECD patent database for G20 countries to identify dominant sectors and technologies. Energy and transport stand out in terms of the number of patents filed signifying the flow of technical expertise (R&D) and finances in these sectors while sectors such as agriculture, natural resource management, disaster resilience, etc., have not attracted much attention. The study also assesses current initiatives to determine India's technological needs and presents an overview of the initiatives undertaken by the Government of India to promote diffusion of environmentally sound technologies. The study finds that the success of technology transfer depends heavily on the availability of funds, absorption capacity of the recipient country and the differential treatment of technologies in technology transfer frameworks.
Keywords: O32; O44; Q01; Q54; Q55; 330; Climate Change; Environmentally Sound Technologies; Technology Transfer; Financial Barriers; Absorption Capacities; Patent Growth; Emerging Economies